Utilization of Cervical Cancer Screening and Associated Factors among Women in Bhaktapur, Nepal - Nepal, J.; Poudyal, A. K.; Duwal, S.; Gyawali, S.; Basel, P. (Kathmandu University Medical Journal, 2022)
Background Cervical cancer is the most common cancer among women in Nepal causing highest cancer mortality among women of reproductive age. However, it can be prevented through early and regular screening.Objective To assess utilization of cervical cancer screening, its awareness and perception among women, and associated factors.Method A cross-sectional study was conducted where 360 women of age 30-60 years were randomly selected and interviewed from five administrative wards of Bhaktapur municipality.Result Utilization of cervical cancer screening through Pap test or Visual Inspection with Acetic acid was found in 32.2% women and 47.8% were aware of cervical cancer and its screening tests. 100% of them had high level of perceived benefits and facilitators. More than 80% of them had low level of perceived barriers and susceptibility. Women of age group 51-60 years were more likely to perform the screening test (AOR=13.14) whereas unemployed women were at higher odds of performing the test (AOR=3.29). Women who were aware of cervical cancer and its screening were more likely to perform the screening (AOR=53.65). Women having low level of perceived barriers (AOR=5.83) and high level of perceived seriousness (AOR=6.67) were more likely to perform the screening.Conclusion Only one third of women had performed Pap test/VIA and those who were aware of cervical cancer and had high level of perception were more likely to perform the screening. Thus, more rigorous and tailor-made awareness programs should be developed by health program planners to increase the screening rate among younger and working women.